2021
DOI: 10.1182/blood-2021-150069
|View full text |Cite
|
Sign up to set email alerts
|

Gemtuzumab Ozogamicin Plus Midostaurin in Combination with Standard Intensive Induction Therapy in Newly Diagnosed AML: Results from a Phase-I Study

Abstract: Background In newly diagnosed acute myeloid leukemia (AML) with FLT3 mutations (FLT3-mut), the tyrosine kinase inhibitor midostaurin (MIDO) in combination with intensive chemotherapy (IC) is considered standard of care (SoC). Subgroup analyses from the ALFA 0701 trial indicate that the addition of the conjugated CD33 antibody gemtuzumab ozogamicin (GO) to IC increases efficacy in the FLT3-ITD subgroup of patients (pts), providing a rationale for the combined use of MIDO plus GO with IC in newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…There have only been limited conference abstracts of ongoing studies published. [6][7][8] Since both drugs were available at once for newly diagnosed AML patients in real life, and the combining of GO plus MIDO with standard IC did not represent a pharmacological contraindication, we decided to employ and retrospectively evaluate the effectiveness and safety of a GO+MIDO+standard IC in patients treated at two Czech hematological centers.…”
Section: Main Bodymentioning
confidence: 99%
“…There have only been limited conference abstracts of ongoing studies published. [6][7][8] Since both drugs were available at once for newly diagnosed AML patients in real life, and the combining of GO plus MIDO with standard IC did not represent a pharmacological contraindication, we decided to employ and retrospectively evaluate the effectiveness and safety of a GO+MIDO+standard IC in patients treated at two Czech hematological centers.…”
Section: Main Bodymentioning
confidence: 99%
“…The efficacy of two of the drug combinations identified by PINet has been validated in clinical trials or in vivo studies. Röllig et al (2021) demonstrated the synergy between gemtuzumab ozogamicin and midostaurin in newly diagnosed AML in a phase-I clinical trial. Tian et al (2018) found that Emricasan and Ponatinib can synergistically reduce ischemia-reperfusion injury in rat brains.…”
Section: Resultsmentioning
confidence: 96%
“…In the phase I MOSAIC trial, GO was associated with midostaurin and standard 3 + 7 chemotherapy in upfront AML with a cCR of 91% [ 97 ].…”
Section: Harnessing Immunitymentioning
confidence: 99%